1895 N.D. Rev. Codes 1293, Penal Code, ch. 40, §§ 7312-13 - (:unkn) unknown (My University, 1895)
Prohibited the carrying of any slungshot or similar weapon, and the concealed carrying of any firearm or any "sharp or dangerous weapon."
Keywords: CARRY; CARRY - CONCEALED